Manipulus Guttiferarum, II. First record of Clusia ucamira (Clusiaceae) from Venezuelan Guayana - Allende, José Ramón Grande (Phytotaxa, 2017)
As part of a review in progress on the genus Clusia Linnaeus in Venezuela, Clusia ucamira J.E. Nascim. & Bittrich is reported for the first time for that country. Clusia ucamira is quickly distinguished from similar species of Clusia sect. Oedematopus (Planchon & Triana) Pipoly by its hemiepiphitic habit, strongly coriaceous and conspicuously revolute leaves, with a very prominent midvein in the abaxial surface. With this range extension, Clusia ucamira is known, besides from the Amazon basin, from terra firme forest in the Amazonas state of Venezuela, where it grows in oligotrophic soils derived from materials from the Guayana Shield. In Venezuela, this species is to be considered Least Concerned (LC), according to the IUCN Red List categories.